Relationship Marketing Investments as an Entry Point to Enhance Their Engagement With the Banking Brand: From Theory to Practice - Idan, Afrah Raheem; Hussein, Amodah Obaid (Research Parks Publishers, 2025)
The current research aims to uncover the role of Relationship Marketing Investments, represented by (Financial investments, Social investments, Structural investments), as an entry point to enhance customer engagement in the banking brand, represented by (cognitive processing, affection processing, activation processing), among a sample of private bank customers in Diwaniya Governorate, which includes six banks: (Taif Islamic Bank, Gulf Commercial Bank, Bank of Baghdad, United Investment Bank, International Development Bank, Trade Bank Of Iraq‎). To achieve the research objective, which stems from the problem raised, represented by (Can Relationship Marketing Investments enhance customer engagement in the banking brand among the concerned sample?), the research adopted the descriptive analytical method, using the questionnaire as an instrument to collect the necessary data for analyzing the levels of the research variables among the sample. Accordingly, (200) questionnaires were distributed to customers dealing with commercial banks, and (179) questionnaires were retrieved, of which (22) were invalid and not compliant with the required specifications as they were incomplete in response. This indicates that the number of valid questionnaires for analysis reached (157), which is equivalent to (78.5%) of the targeted sample responses, and to analyze these results, the research directed to adopt two packages, namely (SPSS & AMOS.V.27), for extracting The desired results; based on the results reached, the research concluded that there is a meaningful correlation between Relationship Marketing Investments and customer engagement with the banking brand, indicating that customers have a positive preference for dealing with commercial banks to improve customer communication quality through multiple distribution channels such as telephone, email, and social media. This, in turn, enhances positive interaction and builds trustworthy relationships. The research also focused on several recommendations, including the need to improve customer communication channels by adopting different distribution channels, which motivates customers to experience the service and build more positive relationships with them. Additionally, relevant banks should develop specialized training programs for their service providers by focusing on communication and relationship-building skills with customers. And properly trained service providers can provide positive experiences that enhance customer engagement.